Dissemination of Orientia tsutsugamushi and inflammatory responses in a murine model of scrub typhus. - Christian A Keller; Matthias Hauptmann; Julia Kolbaum; Mohammad Gharaibeh; Melanie Neumann; Markus Glatzel; Bernhard Fleischer (Public Library of Science (PLoS), 2014)
Central aspects in the pathogenesis of scrub typhus, an infection caused by Orientia (O.) tsutsugamushi, have remained obscure. Its organ and cellular tropism are poorly understood. The purpose of this study was to analyze the kinetics of bacterial dissemination and associated inflammatory responses in infected tissues in an experimental scrub typhus mouse model, following infection with the human pathogenic strain Karp. We provide a thorough analysis of O. tsutsugamushi infection in inbred Balb/c mice using footpad inoculation, which is close to the natural way of infection. By a novel, highly sensitive qPCR targeting the multi copy traD genes, we quantitatively monitored the spread of O. tsutsugamushi Karp from the skin inoculation site via the regional lymph node to the internal target organs. The highest bacterial loads were measured in the lung. Using confocal imaging, we also detected O. tsutsugamushi at the single cell level in the lung and found a predominant macrophage rather than endothelial localization. Immunohistochemical analysis of infiltrates in lung and brain revealed differently composed lesions with specific localizations: iNOS-expressing macrophages were frequent in infiltrative parenchymal noduli, but uncommon in perivascular lesions within these organs. Quantitative analysis of the macrophage response by immunohistochemistry in liver, heart, lung and brain demonstrated an early onset of macrophage activation in the liver. Serum levels of interferon (IFN)-γ were increased during the acute infection, and we showed that IFN-γ contributed to iNOS-dependent bacterial growth control. Our data show that upon inoculation to the skin, O. tsutsugamushi spreads systemically to a large number of organs and gives rise to organ-specific inflammation patterns. The findings suggest an essential role for the lung in the pathogenesis of scrub typhus. The model will allow detailed studies on host-pathogen interaction and provide further insight into the pathogenesis of O. tsutsugamushi infection.